Prostate cancer invasion is promoted by the miR-96-5p-induced NDRG1 deficiency through NF-κB regulation - Soror, A A; Eshagh, R; Fahim, M R; Jamshidian, A; Monfared, G H (Klinicka onkologie, 2024)
BACKGROUND: The N-myc downstream-regulated gene 1 (NDRG1) has been discovered as a significant gene in the progression of cancers. However, the regulatory mechanism of NDRG1 remained obscure in prostate cancer (PCa). METHODS: The miR-96-5p and NDRG1 expression levels were evaluated in PCa cell lines, and prostate tissues, and validated in public databases by real-time polymerase chain reaction, western blot analysis, and immunohistochemistry. The function of miR-96-5p and NDRG1 were investigated by scratch assay and transwell assays in vitro, and mouse xenograft assay in vivo. The candidate pathway regulated by NDRG1 was conducted by the next-generation gene sequencing technique. Immunofluorescence and luciferase assays were used to detect the relation between miR-96-5p, NDRG1, and NF-kB pathway. RESULTS: Overexpressing NDRG1 suppresses the migration, invasion, and epithelial-mesenchymal transition (EMT) in vitro, and inhibits metastasis in vivo. Moreover, miR-96-5p contributes to NDRG1 deficiency and promotes PCa cell migration and invasion. Furthermore, NDRG1 loss activates the NF-kB pathway, which stimulates p65 and IKBa phosphorylation and induces EMT in PCa. CONCLUSIONS: MiR-96-5p promotes the migration and invasion of PCa by targeting NDRG1 and regulating the NF-kB pathway.
Keywords: Neoplasm Invasiveness; nádorové buněčné linie; Cell Movement; regulace genové exprese u nádorů; mikro RNA; prostate cancer; NF-kappa B; nádory prostaty; mužské pohlaví; Mice; Cell Line, Tumor; Intracellular Signaling Peptides and Proteins; epitelo-mezenchymální tranzice; MicroRNAs; Cell Cycle Proteins; Epithelial-Mesenchymal Transition; NDRG1; proteiny buněčného cyklu; intracelulární signální peptidy a proteiny; Prostatic Neoplasms; zvířata; Humans; Gene Expression Regulation, Neoplastic; miR-96-5p; pohyb buněk; invazivní růst nádoru; myši; EMT; lidé; Male; NF- kB; Animals